Vitrificação de tecido ovariano de fetos bovinos associada ao resveratrol - Rocha, Carina Diniz (2017)
The aim of this study was to analyze the morphology and tissue viability of preantral follicles of bovine fetuses by means of histological analysis, fluorescence probes diacetate diclodihydrofluocein and propidium iodide in confocal microscopy, before and after vitrification / warning procedures without or with antioxidant resveratrol. The ovaries (n=18) were fragmented and the fragments distributed to the control (C) groups, vitrified without resveratrol (SR) and vitrified with resveratrol (CR) at the concentration of 20 μM. The experiment 1, morphological analysis of the preantral follicles included in fragments of ovarian tissues by classical histology was performed. The preantral follicles were quantified and classified according to the developmental stage. The mean percentage of normal follicles was higher (P <0.05) in the group of follicles vitrified with resveratrol than in the vitrified without the addition of the antioxidant. In the group of follicles vitrified with resveratrol the class of primordial follicles had a higher percentage (P <0.05) of normal follicles. In contrast, the secondary follicle class had the lowest percentage (P <0.05) of normal follicles in all treatments. In addition, a negative association was observed between the proportion of viable follicles and the stage of follicular development. The probability of finding viable follicles was higher (P <0.05) in the group of vitrified follicles in the presence of resveratrol and follicles of the group with resveratrol presented 2.5 times more chance of viability after vitrification. The chance of observing normal follicles was higher (P <0.05) in the early stages of follicular development. The diameter of the transitional follicles and their respective oocytes was lower when submitted to the vitrification process with resveratrol (P <0.05). In the primary follicle class, the follicular and oocyte diameters were similar (P> 0.05) between the studied groups. The experiment 2, the tissue viability analysis was performed using a confocal microscopy technique that evaluated the fluorescence levels emitted by DCF and IP. The fluorescence levels emitted by PI in the group of fragments vitrified with resveratrol were similar (P> 0.05) to the control group. The levels of EROs were similar between the vitrified and vitrified groups with resveratrol and lower in relation to the control group. The intensity of fluorescence emitted with the use of both probes decreased (P <0.05) with the increased tissue depth analyzed. In addition, linear regression analysis showed a negative correlation between fluorescence intensity and tissue depth. A positive association (P <0.01) was observed between the degenerate cell levels and the ROS rates produced in the treatments with different depths of ovarian tissue, regardless of treatment and tissue depth, groups showed similarity to low ROS.. The proportion of fragments with high level of EROs was higher in the control group compared to the vitrified groups. In conclusion, resveratrol viii favored the preservation of preantral follicles in the early stages of development when submitted to the vitrification / warning process, as well as to reduce the production of ROS and greater cell viability.